npj Regenerative Medicine - Tata, Purushothama Rao.; Christman, Karen; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Regenerative Medicine considers research covering ways to help the human body repair, replace, and regenerate damaged tissues and organs. The journal covers a broad range of topics including but not limited to: Applications of stem cell biology and therapies for tissue repair, regeneration, and organ transplantation Tissue engineering and advances in biomaterials including acellular approaches for tissue repair and regeneration Cell-based therapies and transplantation Gene therapy and gene editing Studies on the molecular and cellular mechanisms underlying tissue regeneration, repair, and remodeling in classical and non-classical model organisms. Strategies for modulating the immune response, promoting immune tolerance, and preventing rejection in regenerative medicine therapies Bioengineering and regenerative medicine technologies, including innovations in 3D bioprinting technologies and organoids Integrating regenerative medicine approaches with rehabilitation therapies Translational research on preclinical models, animal studies, and clinical trials evaluating the safety and efficacy of regenerative medicine therapies Applications of regenerative medicine approaches for treating age-related degenerative diseases Regenerative medicine ethics and policy The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by regenerative medicine experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Medicine$1 (BResearch.s; Biology$1 (BResearch.s; Immunology; Cytology; Biomaterials; Stem cells; Regenerative medicine; Biomedical Research; Immunology; Cell Biology; Biomaterials; Stem Cell Biology; Regenerative Medicine and Tissue Engineering